INTERACTIVE ALGORITHM FOR SELECTION OF LINEAR OBJECTS ON AERIAL PHOTOGRAPHS AND SATELLITE IMAGES - Э. Н. Seredin; B. A. Zalesky (Informatika)
A new approach to the problem of extraction of linear objects on aerial photographs and satellite images is presented. An interactive algorithm of detection of linear objects by broken lines, based on the developed approach, is offered. The algorithm provides fast detection of linear objects,it is easy tuned and convenient for practical use. It is enough precise and reliable to process middle or low reso-lution aerial photographs and satellite images. Specificity of its parallel program implementation is also described. The developed parallel program implementation allowed to reduce the execution time of the algorithm by several orders. Estimates of execution time of versions of the algorithm, which are intended for video cards, are given in the article.